Prevalence of hyperuricemia in patients with severe obesity and the relationship between serum uric acid and severe obesity: A decade retrospective cross-section study in Chinese adults - Cheang, Chonin; Law, Saikam; Ren, Jieru; Chan, Wengtong; Wang, Cunchuan; Dong, Zhiyong (Frontiers in Public Health, 2022)
Objective: Undoubtedly, the relationship between serum uric acid (SUA) and obesity is less data for Chinese patients with obesity. This study aimed to examine the prevalence of hyperuricemia (HUA) and the association between SUA and patients with obesity. Method: All participants were categorized as Overweight, Obesity I, Obesity II, and Obesity III. In addition, based on SUA concentration, the participants were stratified into four quartiles. The authors used descriptive analysis, independent t-test, ANOVA, correlation analysis, and multiple linear regression models to verify the SUA level and Obesity among Chinese adults. Result: Overall, the estimated prevalence of HUA was 69.8%. In the BMI categories, the prevalence of HUA was 5.1% in overweight, 15.2% in Obesity I, 16.9% in Obesity II, and 32.5% in Obesity III. Correlation analysis shows that SUA is strongly correlated with BMI, waist circumference (WC), and hip circumference (HC). Multiple linear regression analysis shows that high density–lipoprotein cholesterol (HDL-C) is a protective predictor of serum uric acid levels in patients with Obesity. Compared with the overweight, Obesity I, Obesity II, and Obesity III were more likely to have higher levels in the SUA levels. Conclusion: We mainly showed that the serum uric acid levels in Chinese patients with severe Obesity declined slightly as age increased.